Aqueous solution-processed off-stoichiometric Cu–In–S QDs and their application in quantum dot-sensitized solar cells. Issue 20 (11th May 2018) - Chiang, Ya-Han; Lin, Kuan-Yu; Chen, Yu-Hsuan; Waki, Keiko; Abate, Mulu Alemayehu; Jiang, Jyh-Chiang; Chang, Jia-Yaw
Abstract : Off-stoichiometric CuInS2 quantum dots (CuInS2, a mixture of In2 S3 /CuInS2, and a Mn-doped mixture of In2 S3 /CuInS2 ) were prepared in a one-pot reaction, and the corresponding sensitized solar cells exhibit promising photovoltaic performances. Abstract : Aqueous solution-processed methods offer several advantages such as simplicity, low-cost, environmental friendliness, and easy scale up. Herein, we present an ultrafast and convenient aqueous route to prepare off-stoichiometric Cu–In–S quantum dots (QDs) including CuInS2, a mixture of In2 S3 and CuInS2 (In2 S3 /CIS), and Mn-doped In2 S3 /CIS (Mn:Cu–In–S), obtained by simply adjusting the feed ratio of Cu and In precursors in an identical procedure. Such off-stoichiometric QDs were then exploited as photon-harvesters in quantum dot-sensitized solar cells (QDSSCs), which showed superior photovoltaic performance that is dependent on the [Cu]/[In] feed ratio. The QDSSCs sensitized with In2 S3 /CIS QDs exhibited a cell efficiency as high as 7.53%, a more promising performance than that of the device sensitized with CuInS2 QDs (1.0%). Such an improvement of the photovoltaic performance can be attributed to the favorable energy level alignment of the adjoining materials (the TiO2 semiconductor and In2 S3 /CIS QDs). Upon incorporation of Mn 2+ into In2 S3 /CIS under identical conditions, the power conversion efficiency of the Mn:Cu–In–S-based QDSSC reached 8.0% due to a synergistic effect between the In2 S3 QDs and Mn 2+ dopant. Analyses of the Bader charge and projected density of states based on density functional theory (DFT) calculations revealed that the coexistence of In2 S3 and Mn 2+ enhances the electronic coupling at the TiO2 /QD interface, leading to a larger number of photoinduced electrons being injected into TiO2 . Electrochemical impedance spectroscopy and intensity-modulated photocurrent/photovoltage spectroscopy measurements confirmed the slower charge recombination and prolonged electron lifetimes that result in the excellent efficiency of the QDSSC device sensitized with Mn:Cu–In–S QDs.